ความสัมพันธ์ระหว่างการสนับสนุนจากองค์การพยาบาล การรับรู้คุณค่าของงานกับการสร้างสรรค์งานในองค์การพยาบาลตามการรับรู้ของพยาบาลวิชาชีพ โรงพยาบาลสังกัดกระทรวงสาธารณสุข เขตกรุงเทพมหานคร - วรรณภา โอฐยิ้มพราย (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purposes of this research were to study the nursing organizational support, job meaningfulness and nursing organizational creativity of professional nurses and to examine relationships between nursing organizational support, job meaningfulness and nursing organizational creativity as perceived by professional nurses in the hospitals under the jurisdication of the Ministry of Public Health, Bangkok Metropolis. The study subjects consisted of 363 professional nurses who were selected by simple random sampling. The instruments were nursing organizational support, job meaningfulness and nursing organizational creativity of professional nurses questionnaires. These questionnaires were tested for content validity and reliability. The alpha coefficient of nursing organizational support, job meaningfulness, and nursing organizational creativity were .94, .93 and .91, respectively. Statistical methods of frequency, mean, standard deviation and Pearson s product moment correlation coefficient were used to analyzestudy data. Major finding were as follows : 1. Job meaningfulness and nursing organizational creativity as perceived by professional nurses by were at high level while nursing organizational support was perceived as moderate. 2. Nursing organizational support and job meaningfulness were positively related to nursing organizational creativity with significantly at the .05 level (r = .45 and .64).